The Adoption of Fintech Solutions by Small and Medium Enterprises (SMEs) in Ilorin - Kemisola Caroline Olagoke; Amos Ajimati; Tajudeen Sunday Jubril; Ojo Mathew Bamidele (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
This study examined the adoption of Financial Technology (FinTech) solutions by Small and Medium Enterprises (SMEs) in Ilorin, Nigeria, and its impact on financial management and business performance. Specifically, the study assessed the effect of mobile payment systems and evaluated the impact of digital lending platforms on the financial management and performance of SMEs in Ilorin, Nigeria. The study adopted a descriptive survey design using purposive sampling to select 350 SMEs across various sectors in Ilorin metropolis, yielding a population of 8,450 SME operators. A sample of 382 SME owners/managers was drawn using Cochran's formula. Data was collected through structured questionnaires and analyzed using simple linear regression. The analysis confirmed that mobile payment systems significantly enhance financial management efficiency (R² = 0.724, p = 0.000), while digital lending platforms demonstrate a strong positive effect on business performance, explaining 68.2% of the variation (R² = 0.682, p = 0.000). The study concluded that FinTech adoption is a critical driver of SME success, with mobile payment systems improving transaction efficiency and cash flow management, while digital lending platforms enhance access to capital and growth opportunities. The findings emphasize the transformative potential of financial technology in empowering SMEs to overcome traditional banking barriers and achieve sustainable growth. It is recommended that SMEs should accelerate FinTech adoption through strategic partnerships, digital literacy programs, and integration of multiple FinTech solutions to maximize competitive advantage and operational efficiency.